On the authorship and publication dates of the nomina Theraphosa and Theraphosidae (Araneae: Mygalomorphae) - Sherwood, Danniella; Blick, Theo; Gabriel, Ray; Lucas, Sylvia M. (Zootaxa, 2021)
The family Theraphosidae is the most speciose in the infraorder Mygalomorphae Pocock, 1892 with over one thousand described species (World Spider Catalog 2021). The taxonomy of the group has been subjected to considerable attention in modern times, with a focus on delineation based predominantly on genital organ and stridulatory organ morphology which has shown promise, both alongside molecular methods (where possible) and as a stand-alone line of evidence, in stabilising the group (e.g. Hamilton et al. 2016; Fabiano-da-Silva et al. 2020; see also Sherwood 2020). The predominant reference to the family is as Theraphosidae Thorell, 1870 with almost as many references to Theraphosidae Thorell, 1869. This non-congruence of dates is because Tord Tamerlan Teodor Thorell (1830–1901) had his important work On European Spiders published in two parts during its publication by the Royal Society of Upsala in its journal Nova Acta Regiae Societatis Scientiarum Upsaliensis. The first half (pages 1–108 and the supplement I–XIII) was published in 1869 whereas pages 109–242 (despite being dated on the cover page as 1869) were published in 1870 (see Roewer 1942; Bonnet 1945; World Spider Catalog 2021). In the second part, the secretary of the society notes: “L’auteur avait proposé comme titre du présent mémoire: Remarks on Synonyms of European Spiders, preceded by some observations on Zoological Nomenclature and a Review of the European Genera of Spiders; mais, la partie, insérée dans le Tome VII, étant seule présentée à la Société des Sciences le 13 Fevr. 1869, il a été nécessaii’e d’y conformer le titre.” [= The author proposed as the title of this memoir: Remarks on Synonyms of European Spiders, preceded by some observations on Zoological Nomenclature and a Review of the European Genera of Spiders; but, the part, inserted in Volume VII, being the only one presented to the Société des Sciences on 13 Feb. 1869, it was necessary to conform the title to it.].